Can a standardized aptitude test predict training success of apprentices? : Evidence from a case study in Switzerland - Siegenthaler, Michael [Verfasser] (My University, 2011)
"Due to a widely spread distrust in the signalling value of school grades, Swiss employers require external, standardized aptitude test results when recruiting new apprentices. However, the predictive quality of such test results has never been thoroughly researched. Therefore, this case study analyses whether external aptitude tests can improve the quality of predicting success in apprenticeship training. I find that such information is a) not correlated with school grades at the end of compulsory schooling but b) does not add information that would explain either the success in VET schooling (school grades in the first and second year of apprenticeship training), the probability of unexcused vocational school absences or the likelihood of a premature ending of the apprenticeship contract." (Autorenreferat, BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; L 8 Diagnostik / Eignung; Ausbildungsstellenbewerber; Bewerberauswahl; Einstellungsvoraussetzung; Schulleistung; Eignungstest; Schweiz